2021
DOI: 10.1038/s41598-021-85308-0
|View full text |Cite
|
Sign up to set email alerts
|

Co-application of high temperature biochar with 3,4-dimethylpyrazole-phosphate treated ammonium sulphate improves nitrogen use efficiency in maize

Abstract: This study aimed on the increasing nitrogen use efficiency (NUE) of maize via the use of high temperature produced biochar (700 °C). Maize was grown to maturity on two contrasting soils (acidic Cambisol and neutral Chernozem) in pots with a treatment of biochar co-applied with ammonium sulphate stabilised by a nitrification inhibitor (3,4-dimethylpyrazole-phosphate, DMPP) or un-stabilised. The combination of biochar with ammonium sulphate containing DMPP increased maize biomass yield up to 14%, N uptake up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…One of the most problematic issues in modern agriculture is the high quantity of ammonia being released, resulting in a partial loss of the N, which is contained in urea fertilizers [34]; according to the same authors, the best results were obtained with the use of the urease inhibitor NBPT, which can decrease ammonia emissions from urea fertilizers by 30-70% [34]. Corrochano-Monsalve et al (2021) [14] found that application of urea with double inhibitor diminished N losses in the form of NH 3 volatilization by more than 50% compared to single urea application, while the co-application of biochar and ammonium sulphate, with the nitrification inhibitor DMPP, increased N uptake up to 34% and N use efficiency up to 13.7% [35]. Centeno et al (2017) [13], who studied the effects of N fertilization and nitrification inhibitors on vegetative growth, production, and olive oil quality of 'Arbequina' hedgerow and 'Picual' vase-trained orchards, found that the effect of nitrification inhibitor (DMPP) on olive growth or production was not consistent, and N fertilization was not always necessary, since, when leaf N was higher than 2% d.w., fruit d.w., oil content, and oil phenolic content were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most problematic issues in modern agriculture is the high quantity of ammonia being released, resulting in a partial loss of the N, which is contained in urea fertilizers [34]; according to the same authors, the best results were obtained with the use of the urease inhibitor NBPT, which can decrease ammonia emissions from urea fertilizers by 30-70% [34]. Corrochano-Monsalve et al (2021) [14] found that application of urea with double inhibitor diminished N losses in the form of NH 3 volatilization by more than 50% compared to single urea application, while the co-application of biochar and ammonium sulphate, with the nitrification inhibitor DMPP, increased N uptake up to 34% and N use efficiency up to 13.7% [35]. Centeno et al (2017) [13], who studied the effects of N fertilization and nitrification inhibitors on vegetative growth, production, and olive oil quality of 'Arbequina' hedgerow and 'Picual' vase-trained orchards, found that the effect of nitrification inhibitor (DMPP) on olive growth or production was not consistent, and N fertilization was not always necessary, since, when leaf N was higher than 2% d.w., fruit d.w., oil content, and oil phenolic content were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The total N input of agricultural soils is mostly limited and less capable of supplying sufficient N forms, mainly due to the loss of N ions via conversion to gaseous forms (i.e., NH 3 , N 2 O, N 2, and NO) leaching below ground (Khan et al 2022b). Plants can absorb N mostly in the form of ammonium and nitrate from N sources; however, they only make up 2% of the total soil N concentration, and their availability in soils is scarce (Hailegnaw et al 2021). To achieve the high production demands, crop growers have gradually increased the use of inorganic fertilizers in inadequate amounts with less utilization efficiency and output rate (Fig.…”
Section: Biochar Modulates Nitrogen Use Efficiency (Nue)mentioning
confidence: 99%
“…Based on these studies, we evaluated that biochar has the potential to decrease N fertilizer usage and improve its utilization, which will help to decrease N 2 O emission and enhance NUE and crop yield on a sustainable basis. (Xiang et al 2020;Khan et al 2020;Omara et al 2020;Hailegnaw et al 2021;Huang et al 2018a, b;Zhang et al 2020;Sarfraz et al 2017;Zhang et al 2020;Khan et al 2021c;Sun et al 2019a, b;Tang et al 2023;Kimani et al 2021;Khan et al 2022b;Liao et al 2020;Kang et al 2021;Chu et al 2020;Oladele et al 2019a, b;Cao et al 2019;Liu et al 2021a, b, c;Rondon et al 2007;Oladele 2019;Yadav et al 2019;Akhtar et al 2014;Huang et al 2018a, b;Baronti et al 2014;Abbruzzini et al 2019;Zhang et al 2020;Khan et al 2021a;Jing et al 2020;Khan et al 2022b;Bashir et al 2020;Macdonald et al 2014) should be addressed by adapting various agronomic approaches to ensure the improvement of crop nitrogen use efficiency (NUE).…”
Section: Biochar Modulates Nitrogen Use Efficiency (Nue)mentioning
confidence: 99%
“…Ammonium sulfate contains not only essential N nutrients for crops but also sulfur nutrients to promote crop development and metabolism [9,10]. After application in soil, ammonium sulfate will immediately dissociate into available NH4 + and SO4 2-that can be absorbed and used by crops, therefore, it has been widely applied in agriculture [11][12][13]. However, ammonium sulfate accounts for less than 1% of the total N fertilizer variety structure in China, which is far lower than the proportion of ammonium sulfate used in developed countries [14], but the industrial by-product ammonium sulfate has a huge production capacity in China.…”
Section: Introductionmentioning
confidence: 99%